OBRAZ JARATÍWDA KÓRKEM DIALOGTÍŃ ÁHMIYETI (Sh.Seytovtıń «Shırashılar» romanındaǵı Esjan ǵarrı obrazı mısalında) - Orınbaev, T.; Xorezmova, A. (SCIENCE and SOCIETY, 2025)
This article focuses on the poetic function of dialogues in a work of fiction. The significance of dialogues in creating the character of old man Yeszhan in Sh. Seitov's novel "The Torchbearers" is examined. By studying the dialogues in the novel, the distinctive features of old man Yeszhan's character are revealed.